Supervisi Berbasis Teknologi: Solusi untuk Pengembangan Guru di Era Digital - Sahudi Sahudi (Pascasarjana Universitas Qomaruddin, 2024)
This study aims to examine the implementation of technology-based supervision in improving teacher competence and professionalism in the digital era. The case study was conducted in five Private Madrasah Tsanawiyah (MTsS) in Gresik Regency, using a qualitative approach. Data were collected through interviews, observations, and document analysis, then analyzed using thematic techniques. The results showed that technology-based supervision, through platforms such as Google Classroom, Zoom, and WhatsApp, had a positive impact on teacher performance and professionalism. In the performance aspect, there was an increase in online classroom management skills, preparation of digital-based lesson plans, and student evaluation. Meanwhile, in terms of professionalism, teachers showed high enthusiasm for developing technological skills, exploring new learning methods, and adapting to technological demands. Constraints include limited internet access, lack of technology training and limited devices. However, opportunities in the form of principal support, allocation of special funds, and adequate infrastructure enable the optimization of technology-based supervision. This study supports the literature which states that the use of technology in supervision improves the quality of teaching and professional interactions. In conclusion, technology-based supervision plays an important role in meeting the needs of education in the digital era and provides solutions to the challenges of supe.